2007
DOI: 10.1074/jbc.m609493200
|View full text |Cite
|
Sign up to set email alerts
|

EHD1 and Eps15 Interact with Phosphatidylinositols via Their Eps15 Homology Domains

Abstract: The C-terminal Eps15 homology domain-containing protein, EHD1, regulates the recycling of receptors from the endocytic recycling compartment to the plasma membrane. In cells, EHD1 localizes to tubular and spherical recycling endosomes. To date, the mode by which EHD1 associates with endosomal membranes remains unknown, and it has not been determined whether this interaction is direct or via interacting proteins. Here, we provide evidence demonstrating that EHD1 has the ability to bind directly and preferential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 63 publications
2
60
0
Order By: Relevance
“…We and others have demonstrated that in vitro, EHD proteins can interact with an array of different phosphoinositides (Blume et al, 2007;Daumke et al, 2007;Naslavsky et al, 2007). Indeed, full-length EHD proteins and EH domains (by sensitive NMR studies) display broad specificity for phosphoinositides.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We and others have demonstrated that in vitro, EHD proteins can interact with an array of different phosphoinositides (Blume et al, 2007;Daumke et al, 2007;Naslavsky et al, 2007). Indeed, full-length EHD proteins and EH domains (by sensitive NMR studies) display broad specificity for phosphoinositides.…”
Section: Discussionmentioning
confidence: 94%
“…Indirect evidence from our laboratory had previously hinted at a potential role for PtdIns(4,5)P 2 in the generation/maintenance of EHD1-associated tubular membranes through activation of Arf6 (Caplan et al, 2002), which leads to PtdIns(4,5)P 2 generation (Honda et al, 1999). These clues were provided from studies showing that either the Arf6 nucleotide status or direct overexpression of the Arf6 GTP-exchange factor (GEF) EFA6 or the Arf6 GTPase-activating protein ACAP1 led to a loss of EHD1-associated tubular membranes (Caplan et al, 2002).We and others have demonstrated that in vitro, EHD proteins can interact with an array of different phosphoinositides (Blume et al, 2007;Daumke et al, 2007;Naslavsky et al, 2007). Indeed, full-length EHD proteins and EH domains (by sensitive NMR studies) display broad specificity for phosphoinositides.…”
mentioning
confidence: 99%
“…In this study, we highlight a previously undescribed role for the Cterminal EHD protein, EHD3, in the regulation of endosome-toGolgi transport. EHD3 would most likely be categorized as being involved in recruitment because: (1) its C-terminal EH domain, present in other EHD family members, is known to bind to proteins containing NPF motifs (reviewed by Naslavsky and Caplan, 2005;Grant and Caplan, 2008); (2) EHD3 is an ATP-binding protein (Daumke et al, 2007;Lee et al, 2005;Naslavsky et al, 2006); and (3) EHD3 can bind to lipids and membranes directly (Blume et al, 2007;Naslavsky et al, 2007). Indeed, not only EHD3, but its early endosomal interaction partner, rabenosyn-5, as well as STX13, an endosomal SNARE protein, also control earlyendosome-to-recycling-endosome and endosome-to-Golgi trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…For example, EHD3 depletion disrupts Shiga toxin delivery from the EE/SE to the Golgi (Naslavsky et al, 2009) and impairs transferrin receptor targeting to the ERC (Naslavsky et al, 2006). While the EHD3 mechanism of action is currently unknown, the EHD ATP-binding G domain is critical for phospholipid binding and membrane recruitment (Blume et al, 2007;Daumke et al, 2007;Naslavsky et al, 2007). Following recruitment to membranes, the EH domain might serve as a nucleation site to recruit auxiliary factors that promote cargo sorting within the EE/SE.…”
Section: Ehd3-dependent Sorting Decisions From the Ee/sementioning
confidence: 99%